2017
DOI: 10.1016/j.apr.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Tree bark as bioindicator of metal accumulation from road traffic and air quality map: A case study of Chiang Mai, Thailand

Abstract: Trees have been recognized as air quality bioindicators, but they have still not been fully implemented in tropical areas. In this study, bark of Cassia fistula was used to inspect accumulation of air pollutants (metals) emitted from road traffic in the city of Chiang Mai, Thailand. The mean concentrations of metal accumulated on tree bark (ng/cm 2) in descending order were Al (1,238) > Fe (707) > Zn (162) >> Cu (21.1) >> Pb (6.37) > Cr (2.14). Correlations of Enrichment Factors: EF TS (metal concentrations on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 36 publications
(55 reference statements)
0
13
0
1
Order By: Relevance
“…For example, the highest concentration of Ba, Cu, and Zn were observed in HYO, while Pb, Ni, and V were elevated at CHI. According to Fijuwara et al [51], Pb, Zn, and Ba are traffic markers, while Janta and Chantara [1], concluded that Cr, Pb, Cu, and Zn come mainly from vehicular sources. In addition, Querol et al [52] suggested that Sb, Cu, Zn, Ba, and Fe are markers of brake or other vehicular parts wear and may be considered as indicators of re-suspension caused by traffic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the highest concentration of Ba, Cu, and Zn were observed in HYO, while Pb, Ni, and V were elevated at CHI. According to Fijuwara et al [51], Pb, Zn, and Ba are traffic markers, while Janta and Chantara [1], concluded that Cr, Pb, Cu, and Zn come mainly from vehicular sources. In addition, Querol et al [52] suggested that Sb, Cu, Zn, Ba, and Fe are markers of brake or other vehicular parts wear and may be considered as indicators of re-suspension caused by traffic.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution and atmospheric deposition of toxic trace elements have become a major environmental concern around the world because of its adverse effect on human health and the environment [1][2][3]. Among major urban air pollutants, airborne particulate matter (PM), in inhalable coarse particles (PM 10 -particles that have aerodynamic diameters less than or equal to 10 µm) or particularly fine particles (PM 2.5 -aerodynamic diameters of 2.5 µm or less) [4] show potential risk to the health human causing premature mortality and cardiovascular diseases [5].…”
Section: Introductionmentioning
confidence: 99%
“…The heavy metal concentrations in the outer bark were higher than in other organs. This result was much clearer in the samples taken from the direction of high traffic volume, and the factors playing a role in these results are mainly different organelle structure, particle materials, and particles' contamination with traffic-borne heavy metals (Janta et al 2016;Janta and Chantara 2017;Sevik et al 2019c). In previous studies, it was determined that the air metals in the air adhere to and infect the particle materials and the heavy metal concentrations in plants increased because of the accumulation of these particles on the plant (Mossi 2018;Sevik et al 2019d).…”
Section: Resultsmentioning
confidence: 93%
“…As a result of this adaptation, the bark of some tree species contains volatile oils and is waterproof [10]. Tree bark is also used as a bio-identifier of metal accumulation from road traffic [11,12]. It plays an important role in the accumulation of dichlorodiphenyltrichloroethane (DDT) from agricultural regions [13].…”
Section: Introductionmentioning
confidence: 99%